Developing Communicative Competence of Esp Learners - Muratovna, Kuldasheva Malika (International Journal on Human-Computing Studies, 2023)
It is necessary to talk about communicative competence as one of the main goals of teaching English. The goal of education in all types of educational institutions is not a foreign language system, but the use of foreign language in the process of communication. The article deals with the issues based on the theory of communicative approach in teaching foreign languages, describe the components of communicative competence and their characteristics, provides various forms and methods for developing communicative skills among students of a technical university.